The US and Trans-Atlantic relations: On the difference between dominance and hegemony - David P. Forsythe (Danish Institute for International Studies (DIIS), 2005)
It is important to distinguish hegemony from dominance, as various authors like Machiavelli, Gramsci, and Nye have argued. This distinction allows one to appreciate that the first Bush Administration attempted to be a dominant power rather than a hegemonic one. A long list of assertions of essentially unilateral dominant power projections is actually buttressed by two pillars: primary of hard power but also American exceptionalism. By comparison to Europe, the George W. Bush version of American exceptionalism emphasizes traditional and absolute U.S. state sovereignty, a corresponding depreciation of international law and organization, parochialism, and non-muscular multilateralism. Because of all this the U.S. is largely responsible for the crisis in Atlanticism. The Europeans, however, have made their own contributions to this crisis. The crisis needs to be resolved, as the management of various international problems requires trans-Atlantic cooperation. Fortunately there are signs of movement toward this cooperation, although the signals are mixed on the U.S. side.
Keywords: 330